2012
DOI: 10.5888/pcd9.110171
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Change in Aerobic Fitness and Weight on Prevalence of Metabolic Syndrome

Abstract: IntroductionThe metabolic syndrome is the clustering of several cardiometabolic risk factors that can lead to the development of coronary heart disease and type 2 diabetes. We evaluated whether a change in aerobic fitness resulting from a lifestyle intervention could significantly change the odds of metabolic syndrome prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…19,21 Gestational obesity and excessive maternal weight gain are associated with macrosomia, postdates pregnancy and high rates of CD. 9,11 ACOG recommends that pregnant women should exercise moderately for 30 minutes on most days of the week. However, very few women meet the minimum recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,21 Gestational obesity and excessive maternal weight gain are associated with macrosomia, postdates pregnancy and high rates of CD. 9,11 ACOG recommends that pregnant women should exercise moderately for 30 minutes on most days of the week. However, very few women meet the minimum recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…9 In 2015, the American College of Obstetricians and Gynecologists (ACOG) emphasized that even if not previously active, pregnancy is an ideal time to adopt lifestyle modifications because women should be seen by a health care provider more frequently than at any other time in their lives. 10 Regular physical exercise or activity promotes and maintains physical fitness, prevents co-morbidities, manages weight, and improves psychological wellbeing.…”
Section: Methodsmentioning
confidence: 99%
“…It is considered to be a precursor of coronary heart disease (CHD) and diabetes [5,6]. It is associated with morbidity and all causes of mortality [7,8]. In the United States (US) CHD is the second leading cause of all natural deaths in young adults ages 18–24 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Few longitudinal studies showed the preventive effect of fitness on metabolic syndrome [8]. Exercise interventions have been shown to be as efficient as the pharmaceutical agents to improve glycaemic control.…”
Section: Introductionmentioning
confidence: 99%